BRONCHIAL ASTHMA IN CHILDREN: CLINICAL COURSE AND TREATMENT APPROACHES - Mahmudov Qudratjon Xamidjon oʻgʻli (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Annotation Bronchial asthma in children is a chronic inflammatory disease of the airways characterized by recurrent episodes of wheezing, coughing, shortness of breath, and chest tightness. The clinical course of pediatric asthma varies depending on age, severity of the disease, and exposure to triggering factors such as allergens, respiratory infections, physical activity, and environmental pollutants. Early diagnosis and continuous monitoring are essential for effective disease control and prevention of complications. Treatment approaches focus on long-term control and relief of acute symptoms through the use of inhaled corticosteroids, bronchodilators, and leukotriene modifiers, combined with avoidance of triggers and patient education. A comprehensive, individualized management strategy improves symptom control, reduces exacerbations, and enhances the quality of life in children with asthma.